(untitled) (Revista Venezolana de Salud Pública, 2018)
Intestinal parasitosis are widely distributed in the world, constituting a public health problem. To evaluate whether the geographical and ecological conditions of the island municipality Almirante Padilla of Zulia State influence the prevalence of intestinal parasitosis of its inhabitants, 87 fecal samples corresponding to individuals of any age and sex were analyzed. Each sample was subjected to direct coproparasitological methods (SSF 0.85% and lugol), formalin-ether concentration method (Ritchie), Kinyoun stain and agar plate technique (Arakaki) for recovery and diagnosis Strongyloides stercoralis larvae. The prevalence of intestinal parasites in the study population was 50.57% (44/87), which prevailed monoparasitism with 52.27% (23/44). Among the parasitized individuals, 29.89% (26/87) of cases corresponded to Chromista Blastocystis sp., followed by Entamoeba complex (13.79%), Endolimax nana (13.79%) and Ascaris lumbricoides (13,79%). Strongyloides stercoralis or intestinal coccidia was not detected. The age group most affected were children aged 2 to 6 years of age (p <0.05). The prevalence and variety of intestinal parasites detected is similar to that reported for other areas of Zulia state where sanitary conditions are similar.